Поліська лексика в романі Володимира Дрозда «Листя землі» - Яворський, Андрій Юрійович; Yavorskyi, Andrii Yu. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У романі-дилогії Володимира Дрозда «Листя землі» проаналізовано лексичні елементи північноукраїнської говірки. Використані автором поліські лексеми систематизовано і прокоментовано з погляду походження. Встановлено, що специфічну поліську лексику складають лексичні діалектизми з прозорою мотивацією, семантичні діалектизми, архаїзми та лексичні запозичення. З’ясовано специфіку використання письменником діалектних елементів та роль діалектизмів у художньому тексті.

Lexical elements of North-Ukrainian dialect in the novel by Volodymyr Drozd “Leaves of the Land” are analyzed. Polissyan lexemes used by writer are systematized and commented in terms of their origin. Specific lexicon includes lexical dialecticisms with transparent motivation, semantical dialecticisms, archaisms and lexical borrowing. The specificity of use of the Polissyan patois elements by the author and the function of the dialectal words in the artistic language are indicated. Elements of dialects V. Drozd uses in very lengthy stories and memories characters (traditional dialogues in the novel, in fact, are absent). Author's speech is focused on literary standard, but it also includes lexical dialecticisms. The writer accurately and fairly reflected the local flavor of the language, topography, mode of life and menage.
Polissyan Vocabulary in the Novel by Volodymyr Drozd “Leaves of the Land”
Keywords: поліська говірка; діалектизм; лексичний діалектизм; семантичний діалектизм; архаїзм; лексичні запозичення; Polissyan dialect; dialecticism; lexical dialecticism; semantical dialecticism; archaism; lexical borrowing